If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9r(r + 1) + 6(1 + -3r) = 0 Reorder the terms: -9r(1 + r) + 6(1 + -3r) = 0 (1 * -9r + r * -9r) + 6(1 + -3r) = 0 (-9r + -9r2) + 6(1 + -3r) = 0 -9r + -9r2 + (1 * 6 + -3r * 6) = 0 -9r + -9r2 + (6 + -18r) = 0 Reorder the terms: 6 + -9r + -18r + -9r2 = 0 Combine like terms: -9r + -18r = -27r 6 + -27r + -9r2 = 0 Solving 6 + -27r + -9r2 = 0 Solving for variable 'r'. Factor out the Greatest Common Factor (GCF), '3'. 3(2 + -9r + -3r2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(2 + -9r + -3r2)' equal to zero and attempt to solve: Simplifying 2 + -9r + -3r2 = 0 Solving 2 + -9r + -3r2 = 0 Begin completing the square. Divide all terms by -3 the coefficient of the squared term: Divide each side by '-3'. -0.6666666667 + 3r + r2 = 0 Move the constant term to the right: Add '0.6666666667' to each side of the equation. -0.6666666667 + 3r + 0.6666666667 + r2 = 0 + 0.6666666667 Reorder the terms: -0.6666666667 + 0.6666666667 + 3r + r2 = 0 + 0.6666666667 Combine like terms: -0.6666666667 + 0.6666666667 = 0.0000000000 0.0000000000 + 3r + r2 = 0 + 0.6666666667 3r + r2 = 0 + 0.6666666667 Combine like terms: 0 + 0.6666666667 = 0.6666666667 3r + r2 = 0.6666666667 The r term is 3r. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3r + 2.25 + r2 = 0.6666666667 + 2.25 Reorder the terms: 2.25 + 3r + r2 = 0.6666666667 + 2.25 Combine like terms: 0.6666666667 + 2.25 = 2.9166666667 2.25 + 3r + r2 = 2.9166666667 Factor a perfect square on the left side: (r + 1.5)(r + 1.5) = 2.9166666667 Calculate the square root of the right side: 1.707825128 Break this problem into two subproblems by setting (r + 1.5) equal to 1.707825128 and -1.707825128.Subproblem 1
r + 1.5 = 1.707825128 Simplifying r + 1.5 = 1.707825128 Reorder the terms: 1.5 + r = 1.707825128 Solving 1.5 + r = 1.707825128 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + r = 1.707825128 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + r = 1.707825128 + -1.5 r = 1.707825128 + -1.5 Combine like terms: 1.707825128 + -1.5 = 0.207825128 r = 0.207825128 Simplifying r = 0.207825128Subproblem 2
r + 1.5 = -1.707825128 Simplifying r + 1.5 = -1.707825128 Reorder the terms: 1.5 + r = -1.707825128 Solving 1.5 + r = -1.707825128 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + r = -1.707825128 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + r = -1.707825128 + -1.5 r = -1.707825128 + -1.5 Combine like terms: -1.707825128 + -1.5 = -3.207825128 r = -3.207825128 Simplifying r = -3.207825128Solution
The solution to the problem is based on the solutions from the subproblems. r = {0.207825128, -3.207825128}Solution
r = {0.207825128, -3.207825128}
| -4=40/x*20 | | -2(x)=2x-10 | | 2(4+x)=2x+3 | | 0.5r=-15 | | 3-j=-j+3 | | 6q=84 | | x+y+2z=0 | | -34r-8=36 | | 8c-6c-c=11 | | 2k-12=4k | | 5x-8x=5x-8x | | 7x+12=8x | | -7(b+9)-2(10b-5)= | | 3x^2=-20 | | 3(6c+1)-18=16c+3 | | h(t)=-16t+150t+70 | | 4x=20 | | 16x-9-9=3x+18 | | 16c-11c-c+3c-4c=9 | | S-1/8=15/8 | | 4x(-7+7x)= | | h(t)=-16+150t+70 | | 900/432 | | 3x+18=16+-9 | | 6-9(3+5n)= | | -5(y+1)=25 | | -4/7x=28 | | -10(1+6m)-4= | | 14=3h+2 | | 3/1-1/6 | | 90x^2+90=0 | | s+6+s+14=4s-40 |